Analisis Biaya Pemeliharaan Terhadap Pendapatan Petani Kelapa Sawit Di Desa Tanjung Aur Kecamatan Bunga Mas Kabupaten Bengkulu Selatan - Pirwansyah, Ekwin; Herri Fariadi; Evi Andriani (Fakultas Pertanian Universitas Ratu Samban, 2024)
The palm oil plantation in Tanjung Aur Village, Bunga Mas Sub-District, South Bengkulu Regency is one of the agricultural businesses that generates income for the people of Tanjung Aur Village, thus farmers need to pay attention to several maintenance costs. The objectives of this research are (1) To determine the maintenance costs of palm oil, (2) To know the income from palm oil businesses, (3) To analyze the effect of maintenance costs on the income of palm oil farmers in Tanjung Aur Village, Bunga Mas Sub-District, South Bengkulu Regency. The research method used is descriptive quantitative and simple linear regression. The results of this study indicate that the monthly maintenance costs for palm oil that must be incurred amount to Rp. 4,668,057 per month. The income from the palm oil business for each farmer is Rp. 7,693,667 per month. Maintenance costs have an effect on income with a calculated Tcount value greater than the T table value (37.394 > 1.67252).